2000
DOI: 10.1016/s0022-5347(05)67200-x
|View full text |Cite
|
Sign up to set email alerts
|

EXISTENCE OF a Β3-Adrenoceptor AND ITS FUNCTIONAL ROLE IN THE HUMAN URETER

Abstract: The present results provide the first evidence that the beta3-AR subtype is distributed in human ureteral smooth muscle and that it, and beta2-AR, mediate the ureteral relaxation induced by adrenergic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 14 publications
2
19
0
1
Order By: Relevance
“…While we are not aware of β 3 -adrenoceptor mRNA studies on rat or mouse ureter, its expression level in human ureter was reported to be low (Park et al 2000;Matsumoto et al 2013); moreover, in some species including humans, ureter relaxation by β 3 -adrenoceptor agonists has been reported (Park et al 2000;Matsumoto et al 2013). Several studies have reported β 3 -adrenoceptor mRNA in rat bladder, including specifically in its urothelium (Seguchi et al 1998;Fujimura et al 1999;Barendrecht et al 2009;Kullmann et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…While we are not aware of β 3 -adrenoceptor mRNA studies on rat or mouse ureter, its expression level in human ureter was reported to be low (Park et al 2000;Matsumoto et al 2013); moreover, in some species including humans, ureter relaxation by β 3 -adrenoceptor agonists has been reported (Park et al 2000;Matsumoto et al 2013). Several studies have reported β 3 -adrenoceptor mRNA in rat bladder, including specifically in its urothelium (Seguchi et al 1998;Fujimura et al 1999;Barendrecht et al 2009;Kullmann et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…CL 316,243 appears to be a rodent-selective agonist, as its potency to stimulate cAMP formation in transfected CHO cells was much higher at the mouse than at the human β 3 -adrenoceptor (pEC 50 8.7 vs. 4.3) (Hutchinson et al 2006). CL 316,243 has repeatedly been used in studies on the rat (Kaidoh et al 2002;Takeda et al 2000Takeda et al , 2002bTakeda et al , 2003Woods et al 2001) and human urinary bladder (Igawa et al 1999(Igawa et al , 2001) and also in the ureter (Murakami et al 2000;Park et al 2000), esophagus (Sarma et al 2003), colon (Kaumann and Molenaar 1996) and blood vessels (Atef et al 1996;Kuratani et al 1994;Leblais et al 2005). In line with the above differences in potency between mouse and human receptors, it also exhibited a consistently higher potency at rat compared with human tissues.…”
Section: Adrenaline and Noradrenalinementioning
confidence: 99%
“…Ureteral access sheath also can provide protection against elevated renal pressures during routine ureteroscopic stone surgery [23]. In addition, some documents reported that some β-receptor agonist can cause relaxation of the upper urinary tract and reduce the pelvic pressure, such as β2-agonists and β3-agonists [6,9,11,12,13,14,15,18,19,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Major experimental studies on modulating the smooth muscles in the ureter and pelvis in order to reduce pelvic pressure have been carried out in vitro and in vivo. Various pharmacological agents have shown great potential for lowering pelvic pressure, such as isoproterenol, terbutaline, norepinephrine, prostaglandin synthetase inhibitors and adrenaline [6,8,9,10,11,12,13,14,15]. In addition, a great deal of evidence has demonstrated that calcium channel blockers (CCBs) are capable of relaxing the smooth muscle of the ureter and pelvis as well as relieving ureteral colic [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%